Factors affecting Academic Performance of Primary Schools in Ikumba Subcounty, Kabale District. - Christopher, Musinguzi (Kabale University, 2020)
This study was designed to investigate factors affecting academic performance of primary schools in Ikumba sub-county. Emphasis was put on trying to establish the effect of parents’ provision of scholastic materials, teacher quality and homework on pupils’ academic performance in primary schools in Ikumba sub-county Kabale district. The study employed a cross sectional survey design. It ensured that sub groups within the population were represented proportionally within the sample. The validity and reliability of research instruments was established and data was collected from 186 respondents consisting of 120 pupils, 60 teachers and 6 head teachers using the simple random sampling method. To analyze data chi square goodness of fit (x2) test was used with the aim of establishing the relationship between parents’ provision of scholastic materials, teacher quality, homework and academic performance of pupils in primary schools in Ikumba sub-county. The findings showed the existence of a significant relationship between parents’ provision of scholastic materials, teacher quality, homework and academic performance. On the basis of the findings, the study concluded that If all the parents of Ikumba sub-county provided scholastic materials, the children could perform well because these helped the children acquire knowledge, skills, and make learners ready to learn. Quality teachers did also matter. Committed, competent and knowledgeable teachers produced better learning and pupils benefit a lot from them. Most parents helped pupils in doing homework which was very important for academic performance of children because it improved the children’s weak areas and sharpened their minds. Head teachers should regularly conduct school based continuous professional development courses (CPDs) for teachers in order to maintain and update the quality and competence of teachers. Parents should provide conducive places for pupils to do home work from home in order to help them concentrate and do their homework well.